Knowledge and opinions regarding BRCA1 and BRCA2 genetic testing among primary care physicians. Issue 1 (14th November 2019) - Dekanek, Erin W.; Thull, Darcy L.; Massart, Mylynda; Grubs, Robin E.; Rajkovic, Aleksander; Mai, Phuong L.
Abstract: BRCA1 and BRCA2 (BRCA1/2) testing is standard for individuals with personal and/or family history suggestive of hereditary breast and ovarian cancer syndrome. The indications for testing have been expanding. To accommodate the need, incorporation of cancer genetic services into the practice of non‐genetic healthcare providers should be considered. We carried out a survey to evaluate the knowledge and opinions regarding BRCA1/2 testing among primary care providers. The survey was sent to 245 Obstetrics/Gynecology and 97 Family Medicine physicians in the UPMC network. Eighty‐six completed the survey between July 2015 and September 2015. The average correct responses to knowledge questions was 73%. A few respondents reported being completely confident, and 50% reported being somewhat confident, in providing BRCA1/2 ‐related information. Respondents selected genetic specialists and oncologists as the most qualified to provide cancer genetic services. Several perceived barriers and motivating factors to the implementation of BRCA1/2 testing in primary care were identified. The findings from this study suggested that primary care providers were not uniformly ready to provide BRCA1/2 genetic testing. Availability of professional society guidelines and evidence of testing's usefulness might motivate the incorporation of BRCA1/2 genetic testing into primary care practices. These findings would help guide future educational efforts to promote provision of cancer genetic services by non‐genetic professionals. Abstract :